DPSCs Protect Architectural Integrity and Alleviate Intervertebral Disc Degeneration by Regulating Nucleus Pulposus Immune Status - Xiwen Dong; Fanqi Hu; Jing Yi; Yuning Zhang; Chao Liu; Panpan Geng; Han Duan; Chu-Tse Wu; Xuesong Zhang; Hua Wang (Stem Cells International)
Intervertebral disc (IVD) degeneration is the primary cause for low back pain that has a high prevalence in modern society and poses enormous economic burden on patients. Few effective therapeutic strategies are available for IVD degeneration treatment. To understand the biological effects of dental pulp stem cells (DPSCs) on nucleus pulposus (NP) cells, we carried out RNA sequencing, bioinformatic analysis which unveiled gene expression differences, and pathway variation in primarily isolated patients’ NP cells after treatment with DPSCs supernatant. Western blot and immunofluorescence were used to verify these molecular alterations. Besides, to evaluate the therapeutic effect of DPSCs in IVD degeneration treatment, DPSCs were injected into a degeneration rat model in situ, with treatment outcome measured by micro-CT and histological analysis. RNA sequencing and in vitro experiments demonstrated that DPSCs supernatant could downregulate NP cells’ inflammation-related NF-κB and JAK-STAT pathways, reduce IL-6 production, increase collagen II expression, and mitigate apoptosis. In vivo results showed that DPSCs treatment protected the integrity of the disc structure, alleviated extracellular matrix degradation, and increased collagen fiber expression. In this study, we verified the therapeutic effect of DPSCs in an IVD degeneration rat model and elucidated the underlying molecular mechanism of DPSCs treatment, which provides a foundation for the application of DPSCs in IVD degeneration treatment.